Photolysis mechanism of sulfonamide moiety in five-membered sulfonamides: A DFT study. (April 2018) - Ge, Pu; Yu, Hang; Chen, Jingwen; Qu, Jingping; Luo, Yi
Abstract: Quantum chemical calculations have been performed to investigate the photolysis mechanism of relatively susceptible sulfonamide moiety of five-membered sulfonamide (SA) antibiotics, such as sulfamethoxazole, sulfisoxazole, sulfamethizole, and sulfathiazole. The results show that the ·OH-mediated indirect photolysis of sulfonamide linkage has two possible multi-step reaction pathways, viz., H-abstraction and electrophilic C1-attack, which is contrast to previously reported one-step cleavage manner. The newly proposed indirect photolysis mechanisms could be applied to six-membered SAs such as sulfadimethoxine. It has been found that the dissociation of SN bond is easier in direct photolysis than ·OH-mediated indirect photolysis. Wiberg bond index and LUMO-HOMO energy gap are investigated to clarify the origin of the discrepant reactivity of sulfonamide moiety of SAs at singlet and triplet states. In comparison with singlet states, the SN bond of SAs is weaker at triplet states of SAs and thus results in higher reactivity of sulfonamide moiety, as also suggested by smaller LUMO-HOMO energy gap. This study could add better understanding to the photolysis mechanisms of SAs, which would be also helpful in utilizing quantum chemistry calculation to investigate the behavior and fate of antibiotics in the aquatic environment. Graphical abstract: Image 1 Highlights: The SN cleavage of five-membered sulfonamides in indirect photolysis is multi-step process rather than one-step process. H-abstraction and C1-attack reaction serve as two possible multi-step pathways. The two proposed indirect pathways can also be applied to six-membered sulfonamides such as sulfadimethoxine. SO2 may be produced in the .·OH-mediated degradation of five-membered sulfonamides. For the photolysis of SN cleavage of sulfonamides, the direct photolysis of is significantly easier than ·OH-mediated indirect dissociation manner.